From inflammation to malignancy: ginsenosides as a bridge between traditional healing and modern therapies for periodontitis and oral cancer - Meysam Hosseinzadeh; Hassan Bazvand; Ehsan Gravand; Mohammad Hossein Pourhanifeh (Phytomedicine Plus, 2025)
Periodontal disease and oral cancer are major global health issues, with periodontitis leading to tooth loss and linked to systemic diseases. Oral squamous cell carcinoma (OSCC), a leading cause of morbidity and mortality, is strongly associated with risk factors such as poor oral hygiene, smoking, and alcohol consumption. There is a connection between these conditions, as periodontal disease may elevate the risk of oral cancer through chronic inflammation and microbial dysbiosis. Ginsenosides, bioactive compounds found in ginseng, show promise for their therapeutic effects on both conditions. These saponins possess anti-inflammatory, antioxidant, and anticancer properties, and recent studies indicate they can modulate immune responses, inhibit tumor growth, and lower inflammatory markers in periodontitis by suppressing pro-inflammatory cytokines like IL-6 and TNF-α. This review discusses the therapeutic potential of ginsenosides in treating periodontitis and oral cancer, focusing on the underlying mechanisms.